The mysteries collection - Blyton, Enid (Dean, 2002)
In these three adventures, the irrepressible five find-outers - Larry, Daisy, Pip, Bets and Fatty, plus Buster the dog solve three exciting mysteries, in spite of the efforts of PC Goon to stop them...